HUBUNGAN KOMUNIKASI INTERPERSONAL PERAWAT DENGAN KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS TIPE 2 - Syaripudin, Ahmad (Ensiklopedia of Journal, 2024)
Abstract: Panarung Health Center, in the period 2022-2023, recorded a population of 856 patients diagnosed with type 2 Diabetes Mellitus (DM). The purpose of the study was to determine the relationship between nurse interpersonal communication and medication compliance in patients with type 2 diabetes mellitus. The research design used in this study was cross sectional. The research was conducted at the Panarung Health Center in Palangka Raya. The research was conducted in August 2023. The study population was all DM patients at the Panarung Palangka Raya Health Center. The sample amounted to 40 respondents who were selected using purposive sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed that there was a relationship between interpersonal communication (p value: 0.001) on compliance with taking medication in diabetic patients. It is suggested that health care institutions can pay attention and become a facilitator for nurses to improve interpersonal communication as one of the supporting factors for treatment adherence of diabetes mellitus patients. Nurses should learn and practice interpersonal communication skills with patients in order to establish a warm interpersonal relationship with patients, and improve treatment compliance and taking medication in patients with diabetes mellitus.Keywords: Diabetes, Interpersonal Communication, Nurses